Analysis of volatile compound from swiftlet raw material using solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC-MS) and e-nose sensor - Nik Fatin Nabilah, Muhammad Nordin; Che Mohd Aizal, Che Mohd; Jalila, Abu; Saiful Nizam, Tajuddin (AIP Publishing, 2024)
Aerodramus fuciphagus, or swiftlets are small insectivorous birds that breed throughout Southeast Asia. Edible birds’ nest (EBN) from the swiftlets’ saliva secretion are valuable in the market. EBN industry in Malaysia are large and recognized for its economic potential. Aroma is one of the factors believed to attract swiftlets to enter and build nests in the birdhouse. This study focused on the identification of volatile organic compounds (VOCs) from the aroma of EBN, feather, and guano as reference samples in a successful swiftlet birdhouse. E-nose technology was used to determine the VOC similarity index based on the reference samples collected. Headspace technique coupled with gas chromatography/mass spectrometry (HS-GC/MS) were performed for the chemical profile identification. The area favored by the population of swiftlet are shown through the similarity index of the e-nose results which are 87.06%, 67.15% and 60.23% obtained from feather, guano and EBN respectively. Next, HS-GC/MS using four types of solid-phase microextraction (SPME) fibers were used in the analysis. PDMS fiber showed the highest efficiency in extracting the VOCs from the reference samples. Pentadecane (15.5%) and 2,4-Di-tert-butylphenol (10.41%) were the main compounds from 16 compounds identified in EBN. Eleven compounds were identified in the feather sample with Heptadecane (7.26%) and Pentadecane (6.14%) as the main compounds, followed by ten compounds extracted from the guano sample, with 2-Bromo dodecane (11.9%) and Hexadecane (7.39%) as the main compounds. From this study, the volatile compounds of the possible natural aroma that attracts the swiftlets into the birdhouse can be identified.